Improving Students’ Reading Comprehension By Using Think-Aloud Strategy - Lilis Sholihah; Jusika Sari (State Institute for Islamic Studies IAIN of Metro, 2018)
The problems of this research is the students are difficult to find the information from the text. The objective of this class action research are: (1) to know how far Think-aloud strategy can improve the students’ reading comprehension and; (2) to know how the process of teaching reading by using Think-Aloud Strategy at eleventh grade of SMK Kartikatama Metro in academic year 2017/2018. The method of this research is clasroom action research that consist of two cycles. The subject of this research is the students of Accounting Class eleventh grade of SMK Kartikatama Metro that consist of 30 students. The research instruments in this research are observation, interview sheets, and test. The result of the data analysis in this research are pre-test until post-test 2 that the average of pre-test was 60.93. Then, the implementation of think-aloud strategy in teaching, there is an increase of 3.65 become 64.58. Then, in the cycle 2 the average of students’ score is 80.17. Based on the teaching and learning activities, pre-test until post-test 2 are increased. From the cycle 2, It is about 80 % of the students can achieve the minimum passing criteria (KKM), so this research is success. The conclusion is the implementation of think-aloud strategy can improve students' reading comprehension.